Exploring the Potential Molecular Mechanism of Scutellaria baicalensis Georgi in the Treatment of Gastric Cancer Based on Network Pharmacological Analysis and Molecular Docking Technology - Tu, Yi; Wu, Quanli; He, Jiarui; Xu, Jiasheng; Yu, Shasha; Wang, Qingfei; Cheng, Yunqi; Yang, Qijun; Xu, Shan; Cao, Yi (Frontiers in Pharmacology, 2021)
Objective: To explore the molecular mechanism of Scutellaria baicalensis Georgi in treating gastric cancer by network pharmacological analysis and molecular docking. Methods: Taking Scutellaria baicalensis Georgi as the object, the active components and corresponding potential drug targets in Scutellaria baicalensis Georgi were obtained from the database of TCM Pharmacological System Analysis Platform (TCMSP). GeneCards/OMIM/DrugBank and other databases were used to collect gastric cancer-related genes, and the obtained genes were intersected with drug targets to obtain the target genes of Scutellaria baicalensis Georgi on gastric cancer. Further， construct the interaction network of Scutellaria baicalensis Georgi active ingredients-target-gastric cancer-related genes. Protein-protein interaction analysis and GO, KEGG enrichment analysis was carried out on target genes. The PubChem website was used to screen the compounds corresponding to the target genes, and the target protein and 3D structure pdb format files were obtained from the PDB database. Finally, the molecular docking calculation was performed by the Autodock Vina program.The in vivo cell experiments on the effect of Scutellaria baicalensis on proliferation and migration of gastric cancer cells was used to determine the therapeutic effect of Scutellaria baicalensis on gastric cancer, and the two genes ESR1 and FOS are the key targets of Scutellaria baicalensis on gastric cancer. Results: A total of 10 gastric cancer-related target genes were screened out, and Scutellaria baicalensis Georgi contained 10 active compounds targeting 10 gene sites. There are 30 effective compounds in Scutellaria baicalensis Georgi targeted to treat gastric cancer, and there are 91 corresponding targeting gene sites, involving a total of 10 pathways. The results of molecular docking show that ESR1, FOS, and Scutellaria baicalensis Georgi have good binding free energy and docking fraction. The docking fraction of FOS is -4.200 and the binding free energy is -27.893kcal/mol. The docking fraction of ESR1 is -5.833 and the binding free energy is -30.001kcal/mol.The effect of Scutellaria baicalensis Georgi on gastric cancer was verified by in vitro cell experiments and western blotting. Conclusion: Scutellaria baicalensis Georgi can target and regulate multiple signal pathways by acting on ESR1 and FOS gene loci, thus having a potential therapeutic effect on gastric cancer.